Staging Neck Dissection and Transoral Robotic Surgery Treatment Algorithm in Palatine Tonsil Cancer. (21st November 2017) - Spellman, Joseph; Sload, Ryan; Kim, Paul; Martin, Peter; Calzada, Gabriel
Abstract : Objective: This study introduces a treatment algorithm based on staging neck dissection to identify patients with palatine tonsil squamous cell carcinoma who can be effectively treated with single‐modality transoral robotic surgery while maintaining quality of life. Study Design: Retrospective case series. Setting: Kaiser Permanente Southern California Medical Group from 2012 to 2017. Subjects and Methods: Patients with early‐stage (T1/2) palatine tonsil squamous cell carcinoma with clinically and radiographically N0 necks underwent staging neck dissection. Those with pN2/3 disease or extracapsular extension on final pathology were triaged to definitive chemoradiation treatment. Patients with confirmed pN0/1 necks without extracapsular extension were treated definitively with transoral robotic surgery. Results: Nineteen patients with cN0 disease underwent selective neck dissection. All were p16 positive. Of these, 14 had pathologically confirmed N0/1 necks without extracapsular extension and were treated with primary surgical resection via transoral robotic surgery. Clear margins were obtained on all patients. There were no significant intra‐ or postoperative complications. No patients required gastrostomy tube or tracheostomy placement. Mean and median follow‐up was 28 months with no recurrences to date. Conclusion: Up‐front staging neck dissection accurately triages low‐risk patients, determining candidates for single‐modality definitive treatment with transoral robotic surgery. This approach provides excellent survival outcomes and minimal morbidity and maintains quality of life among appropriately selected patients with palatine tonsil cancer.